The Mystery of The Cat Disappearance from The Shio - Umardifa, Floria Egidia; Fika, Kalya Fausta (Confucius Institute Universitas Sebelas Maret, 2023)
The Chinese zodiac system, known as shio, is a symbolic representation of the years based on the cycle of 12 animals that influences Chinese belief and culture. Immortals were sent to the human world to announce that the rank of animals depends on the order in which they pass through the gates of heaven. However, not many people understand that cats used to participate in the race to pass through the gates of heaven, although, in the end, cats were not included in the 12 ships. Therefore, this paper aims to tell the story and introduce and give an in-depth dimension to the traditional culture and heritage that continues to be inherited from generation to generation. In this research, we use qualitative research methods by making a detailed and accurate description of a subject so that readers can easily understand why cats are not represented in the Chinese ship. The results of this study can be concluded that there is competition between several animals to the gates of heaven, which ultimately becomes the Chinese calendar system as an annual representation, a symbol of human characteristics which is still used to predict luck, sustenance, and can even expect a thing that is much sought after in young people, namely romantic relationships.